Pseudo Wigner–Ville Time-Frequency Distribution and Its Application to Machinery Condition Monitoring - Young S. Shin; Jae-Jin Jeon (Shock and Vibration, 1993)
Machinery operating in a nonstationary mode generates a signature that at each instant of time has a distinct frequency. A Time-frequency domain representation is needed to characterize such a signature. Pseudo Wigner–Ville distribution is ideally suited for portraying a nonstationary signal in the time-frequency domain and is carried out by adapting the fast Fourier transform algorithm. The important parameters affecting the pseudo Wigner–Ville distribution are discussed and sensitivity analyses are also performed. Practical examples of an actual transient signal are used to illustrate its dynamic features jointly in time and frequency.